Learning to Live Through Loss: When Job Loss Triggers Grief - Carolyn S. Wilken (EDIS)
FCS-2264, a 3-page fact sheet by Carolyn Wilken, addresses the genuine grief many people feel on losing their jobs and gives suggestions for productively working through it and moving on to new employment. Published by the UF Department of Family, Youth and Community Sciences, November 2006.